1984
DOI: 10.1046/j.1467-6427.1984.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teams reflect family dysfunction

Abstract: Therapists frequently have strong negative reactions to their patients. The view is put forward in this paper that such reactions may be harmful to patients if they are not acknowledged. However, when we, as therapists, are able to recognize our own reactions, they could prove to be a valuable source of information about those people we are trying to help. Three cases are described in which clinical teams behaved in negative ways towards families, who, as a result, did not receive the appropriate treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(10 reference statements)
0
9
1
Order By: Relevance
“…The aim of reconvening the meeting, besides imparting information, is to ensure that the team continues to have a shared view of the problem and way forward. As was found in the R family, it is not unusual for Family therapy in paediatric settings 22 1 splits to develop in teams, which can mirror the processes occurring in the family (Berkowitz and Leff, 1984). The meeting allows for tensions between professionals to surface, be recognized and worked through.…”
Section: Reconvening the Professional Staff Groupmentioning
confidence: 95%
See 1 more Smart Citation
“…The aim of reconvening the meeting, besides imparting information, is to ensure that the team continues to have a shared view of the problem and way forward. As was found in the R family, it is not unusual for Family therapy in paediatric settings 22 1 splits to develop in teams, which can mirror the processes occurring in the family (Berkowitz and Leff, 1984). The meeting allows for tensions between professionals to surface, be recognized and worked through.…”
Section: Reconvening the Professional Staff Groupmentioning
confidence: 95%
“…With reference to the ward team, we felt that splits were occurring over how John should be managed, owing to differing perceptions of the aetiology to the problem. These splits appeared to be undermining any effective intervention and we hypothesized that this could be the result of the team reflecting dysfunctions within the family (Berkowitz and Leff, 1984). The involvement of the ward psychologist (A.M.J.)…”
Section: The Structural Hypothesismentioning
confidence: 99%
“…In this context counter-transference reactions on the part of the network are likely to reproduce the dynamics of the original family relationships. Berkowitz & Leff (1984) described the power and concreteness of these unconscious influences and the importance of being able to understand and cope with them if the professionals are to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…3. As a method of exploring how the deficiencies of the professional network can sometimes exacerbate the placement difficulties (Berkowitz & Leff, 1984) Our professional setting is an out-patient based NHS Child Psychiatric Clinic with a long-standing, stable, multidisciplinary team from a variety of professional and theoretical backgrounds. Over many years we have developed a shared way of working which amalgamates psychoanalytic ideas with family therapy concepts.…”
mentioning
confidence: 99%
“…Exceptions include those papers already mentioned and a few others such as Berkowitz and Leff (1984), who have focused on the reactions of clinical teams to families and emphasized the value of these reactions as providers of information about relationships in the family. This is in similar vein to Palazzoli et al (1978Palazzoli et al ( , 1980 and to Cecchin (1987), who have suggested that how the therapist 'feels' provides information not only about the family but more particularly about the therapist-family relationship.…”
Section: Shared Aspects Of Practicementioning
confidence: 99%